POLITICAL ECONOMY OF TRADE PROTECTION AND LIBERALISATION: IN SEARCH OF AGENCY-BASED AND HOLISTIC FRAMEWORK OF POLICY CHANGE - TROFIMOV, Ivan D. (Theoretical and Practical Research in Economic Fields; Vol 8 No 2 (2017): TPREF, Volume VIII, Issue 2(16), Winter 2017DO - 10.14505/tpref.v8.2(16).04, 2017)
The paper provides comprehensive review of alternative explanations of the trade policy formation, associated rise of trade protectionism, and difficulties of trade liberalization. Normative economic, systemic, public interest, political, institutional and constitutional economic theories of trade policy, together with political science models of trade cooperation are considered. The paper shows that current research in the area tends to accentuate the factors that entrench trade protectionism, while paying insufficient attention to the role of agency, policy dynamics and informal institutions that may bring in trade liberalization. Requirements for holistic and dynamic analysis of trade policy are outlined.